Islam dan Toleransi Beragama dalam Masyarakat Muslim Kanayatn Dayak di Kalimantan Barat - Hermansyah, Hermansyah (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
The object of this study is Islam in Dayak communities; a subject that is rarely being studied. It tries to expose some interesting facts about Islam in these isolated communities. Many have hitherto thought that the Dayak communities are primitive with no particular affiliation to any formal religion. This paper tries to show the reverse. The truth is that these communities do even have reasonably developed view of Islam especially that which has to do the problem of tolerance and social life. The basic premise that this paper adopts is that a practice is form of paradigm; the way a particular society performs social life reflects their orientation of religious understanding. Hence, although the Dayak communities do not have paradigmatic understanding of Islamâin the strictest sense of the wordâthey do nonetheless have a practical discourse that emerge out of their unique and perhaps simple understanding of their religion. Relevant to the study of this object is the issue of community identity and how this issue is related to the religious identity. Hence, the paper is interested in exposing the tension between the two identities in the context of the Dayak communities in West Kalimantan.